2016
DOI: 10.1002/1873-3468.12154
|View full text |Cite
|
Sign up to set email alerts
|

Identification of seco‐clavilactone B as a small‐molecule actin polymerization inhibitor

Abstract: Edited by Judit OvadiPhenotype-based chemical screening is an attractive strategy for the identification of bioactive compounds. We searched for a compound that induces cellular morphological change and identified a novel compound that we named seco-clavilactone B (Seco-CB). Treatment with Seco-CB decreased the ratio of filament actin (F-actin) to globular actin (G-actin). An in vitro actin polymerization assay revealed that Seco-CB inhibited actin polymerization directly. Further analysis demonstrated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Signals were detected with ECL using Western Lightning Plus-ECL (PerkinElmer, Inc., Waltham, MA, USA) and Immobilon Western Chemiluminescent HRP substrates (Merck KGaA). Protein bands were quantified in ImageJ (National Institutes of Health, Bethesda, MD, USA) [ 34 , 35 , 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Signals were detected with ECL using Western Lightning Plus-ECL (PerkinElmer, Inc., Waltham, MA, USA) and Immobilon Western Chemiluminescent HRP substrates (Merck KGaA). Protein bands were quantified in ImageJ (National Institutes of Health, Bethesda, MD, USA) [ 34 , 35 , 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cell culture. HT1080 human fibrosarcoma (Japanese Collection of Research Bioresources Cell Bank, Osaka, Japan), 293T (RIKEN BioResource Center, Tsukuba, Japan), A549 human lung adenocarcinoma (RIKEN BioResource Center) (37)(38)(39)(40), PANC1 human pancreatic adenocarcinoma (RIKEN BioResource Center) and MDA-MB-231 human breast adenocarcinoma cell lines, which was gifted by Professor Masakazu Toi (Kyoto University Graduate School of Medicine, Kyoto, Japan), were all cultured in Dulbecco's modified Eagle's medium (DMEM; Nissui Pharmaceutical Co., Ltd, Tokyo, Japan) supplemented with 6% (v/v) fetal bovine serum (Cosmo Bio Co. Ltd., Tokyo, Japan), 100 U/ml penicillin G, 100 mg/l kanamycin, 600 mg/l L-glutamine, and 2.25 g/l NaHCO 3 at 37˚C in a humidified incubator with 5% CO 2 . The LoVo human colon adenocarcinoma cell line was cultured in RPMI-1640 medium (Nissui Pharmaceutical Co., Ltd) supplemented with 10% (v/v) fetal bovine serum, 105 U/ml penicillin G, 105 mg/l kanamycin, 314 mg/l L-glutamine, and 2.25 g/l NaHCO 3 at 37˚C in a humidified incubator with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Next, we completed the enantioselective total synthesis of the natural enantiomers of 1 and 2 . In collaborative research with a biology group, we showed that synthetic analog 6 , called seco‐clavilactone B, is a novel actin polymerization inhibitor and can serve as a bioprobe for clarifying cytoskeletal dynamics . Later, two total syntheses of clavilactones were published by the Li group and the Yoshimitsu group .…”
Section: Figurementioning
confidence: 99%